The human phosphatase CDC14A modulates primary cilium length by regulating centrosomal actin nucleation - Uddin, Borhan; Chen, Nan-Peng; Neuner, Annett; Ruppert, Thomas; Lorenz, Holger; Pereira, Gislene; Schiebel, Elmar; Partscht, Patrick (EMBO reports, 2019)
Abstract CDC14A codes for a conserved proline-directed phosphatase, and mutations in the gene are associated with autosomal-recessive severe to profound deafness, due to defective kinocilia. A role of CDC14A in cilia formation has also been described in other organisms. However, how human CDC14A impacts on cilia formation remains unclear. Here, we show that human RPE1 hCDC14APD cells, encoding a phosphatase dead version of hCDC14A, have longer cilia than wild-type cells, while hCDC14A overexpression reduces cilia formation. Phospho-proteome analysis of ciliated RPE1 cells identified actin-associated and microtubule binding proteins regulating cilia length as hCDC14A substrates, including the actin-binding protein drebrin. Indeed, we find that hCDC14A counteracts the CDK5-dependent phosphorylation of drebrin at S142 during ciliogenesis. Further, we show that drebrin and hCDC14A regulate the recruitment of the actin organizer Arp2 to centrosomes. In addition, during ciliogenesis hCDC14A also regulates endocytosis and targeting of myosin Va vesicles to the basal body in a drebrin-independent manner, indicating that it impacts primary cilia formation in a multilayered manner.